2001
DOI: 10.1165/ajrcmb.24.5.4333
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts from Idiopathic Pulmonary Fibrosis and Normal Lungs Differ in Growth Rate, Apoptosis, and Tissue Inhibitor of Metalloproteinases Expression

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disorder characterized by fibroblast proliferation and extracellular matrix accumulation. However, studies on fibroblast growth rate and collagen synthesis have given contradictory results. Here we analyzed fibroblast growth rate by a formazan-based chromogenic assay; fibroblast apoptosis by in situ end labeling (ISEL) and propidium iodide staining; percent of alpha-smooth muscle actin (alpha-SMA) positive cells by fluorescence-activated cell sorter; and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
262
4
14

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(299 citation statements)
references
References 28 publications
19
262
4
14
Order By: Relevance
“…It is known that the majority of fibrosis progression of UIP demonstrates a slow progression over many years. 44 This is in accord with the studies which show that cultured fibroblasts from patients with IPF/UIP have low growth rate compared with that of normal controls 49,50 and the proliferative activity of fibroblasts in fibroblastic foci of UIP tends to be lower than those in intraluminal buds of OP by Ki-67 immunoreactivity. 51 We also previously reported that deposition of tissue inhibitors of metalloproteinase-2, which inhibits cell migration, 52 is greater in fibroblastic foci of UIP than in intraluminal buds of OP.…”
Section: Discussionsupporting
confidence: 86%
“…It is known that the majority of fibrosis progression of UIP demonstrates a slow progression over many years. 44 This is in accord with the studies which show that cultured fibroblasts from patients with IPF/UIP have low growth rate compared with that of normal controls 49,50 and the proliferative activity of fibroblasts in fibroblastic foci of UIP tends to be lower than those in intraluminal buds of OP by Ki-67 immunoreactivity. 51 We also previously reported that deposition of tissue inhibitors of metalloproteinase-2, which inhibits cell migration, 52 is greater in fibroblastic foci of UIP than in intraluminal buds of OP.…”
Section: Discussionsupporting
confidence: 86%
“…S14). In patients with IPF and asthma, collagens, TIMPs, and profibrogenic cytokines are increased (32,33) whereas the levels of MMPs vary, depending on the stage of the disease (16). Therefore, Pin1 inhibitors, several of which show nanomolar K i and favorable cell permeability (34), may be effective to treat fibrotic diseases of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Profibrotic phenotypes are observed and maintained in vitro in fibroblasts from patients with scleroderma, pulmonary, renal, and colonic fibrosis. [13][14][15] There is some evidence of phenotypic changes in fibroblasts isolated from mucous membrane pemphigoid patients, 16 -18 but whether there are pathological alterations in key aspects of fibroblast behavior, such as motility, contractile function, matrix synthesis, and development of myofibroblast characteristics, has not been investigated. Moreover, whether there are differences in fibroblasts isolated from actively inflamed tissue compared with fibroblasts isolated from clinically uninflamed tissue is unknown.…”
mentioning
confidence: 99%